Sistem Pendukung Keputusan Calon Penerimaan Bantuan Program Indonesia Pintar Menggunakan Metode TOPSIS - Khairunnisa Ika; Ika Yusnita Sari; Elvika Rahmi; Marjones H. H Sihombing (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
The distribution of scholarships is a government program related to tuition assistance given to students who come from underprivileged families as evidenced by the Prosperous Family Card (KKS) to help implement educational equity. The division of students is done to help determine in recommending someone who is eligible to receive a scholarship, a Decision Support System is needed. The determination of current scholarship providers is only based on an analysis of existing data records manually, which allows for errors to occur. From previous observations, a decision support system was created in optimizing the provision of scholarships to SMA Imelda Medan students. This research aims to optimize the results of decisions in providing incentives to students. The method used is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) which can help provide recommendations for scholarship recipients. It is hoped that the use of a Decision Support System (SPK) can assist decisions to be taken in choosing and determining who is the best student to get a PIP scholarship, bearing in mind that so far they have not used a particular method in selecting students so that sometimes decisions are considered less objective and not on target. This method can be used to determine scholarship recipients in the assessment of scholarship acceptance. It can facilitate decisions for 10th grade students of SMA Imelda Medan, proportionally based on the results of student data processing including family cards, parents' occupations, parents' income.